Endothelial microparticle-promoted inhibition of vascular remodeling is abrogated under hyperglycaemic conditions. (November 2017) - Jansen, Felix; Zietzer, Andreas; Stumpf, Tobias; Flender, Anna; Schmitz, Theresa; Nickenig, Georg; Werner, Nikos
Abstract: Background: Endothelial microparticles (EMPs) inhibit vascular remodeling by transferring functional microRNA (miRNA) into target vascular smooth muscle cells (VSMCs). Because EMPs are increased in diabetic patients and potentially linked to vascular complications in diabetes mellitus, we sought to determine whether effects of EMPs generated under high glucose concentration on vascular remodeling might differ from EMPs derived from untreated cells. Methods and results: EMPs were generated from human coronary endothelial cells (HCAEC) exposed to high glucose concentrations in order to mimic diabetic conditions. These EMPs were defined as 'hyperglycaemic' EMPs (hgEMPs) and their miRNA transfer capacity and functional effects were compared with EMPs generated from 'healthy' untreated HCAECs. In vitro, the intercellular transfer of antiproliferative miRNA-126-3p from ECs to VSMCs via EMPs was significantly reduced under hyperglycaemic conditions. Additionally, EMP-mediated inhibition of the miRNA-126-3p target LRP6 and of VSMC migration and proliferation was abrogated, when hgEMPs were used. In vivo, the inhibitory effect of EMPs on neointima formation, VSMC proliferation and macrophage infiltration was abolished in mice treated with hgEMPs. Conclusion: Pathological hyperglycaemic conditions weaken potentially protective intercellular communication mechanisms by affecting EMP content and function. Highlights: EMP based miRNA126 transfer reduces neointima formation via downregulation of LRP6. EMP treatment decreases VSMC proliferation and macrophage infiltration. In hyperglycaemc conditions (hgc) microparticle-based miRNA transfer is impaired. EMP mediated inhibition of vascular neointima formation is abrogated in hgc. EMP effects on VSMC proliferation and macrophage infiltration are abolished in hgc.